2016
DOI: 10.1007/s00227-016-2841-y
|View full text |Cite|
|
Sign up to set email alerts
|

Sex-specific macronutrient foraging strategies in a highly successful marine predator: the Australasian gannet

Abstract: Farewell Spit gannetry in New Zealand. Our results showed intra-and inter-specific variation in the protein, lipid and water composition of prey captured by our sample of 111 Australasian gannets. In addition, we observed significant differences in the Australasian gannets' nutritional niche between seasons. We provide evidence of sex-specific macronutrient foraging strategies in a successful marine predator in the wild. We have shown that in spite of fluctuations in the nutritional composition of foods availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 86 publications
(87 reference statements)
3
42
0
Order By: Relevance
“…A growing body of evidence suggests that vertebrate predators consume prey that varies in their nutritional and energetic compositions (Lenky, Eisert, Oftedal, & Metcalf, ; Machovsky‐Capuska, Coogan, Simpson, & Raubenheimer, ; Machovsky‐Capuska, Priddel et al., ; Malinowski & Herzing, ; Mayntz et al., ). Here, we demonstrated that there is an appreciable variation in the proportional wet mass contribution of P, L, W and PL ratio in the prey species consumed by gannets, which is consistent with previous findings on gannet prey species (Machovsky‐Capuska, Senior, Benn et al., ; Tait et al., ). These results further support previous suggestions on the importance of nutrient content rather than just energetic value of prey alone (Machovsky‐Capuska, Coogan et al., ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A growing body of evidence suggests that vertebrate predators consume prey that varies in their nutritional and energetic compositions (Lenky, Eisert, Oftedal, & Metcalf, ; Machovsky‐Capuska, Coogan, Simpson, & Raubenheimer, ; Machovsky‐Capuska, Priddel et al., ; Malinowski & Herzing, ; Mayntz et al., ). Here, we demonstrated that there is an appreciable variation in the proportional wet mass contribution of P, L, W and PL ratio in the prey species consumed by gannets, which is consistent with previous findings on gannet prey species (Machovsky‐Capuska, Senior, Benn et al., ; Tait et al., ). These results further support previous suggestions on the importance of nutrient content rather than just energetic value of prey alone (Machovsky‐Capuska, Coogan et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…Following Machovsky‐Capuska, Senior, Benn et al. (), linear mixed models (LMMs) were used to evaluate the between‐species variation (quantified as standard deviation— SD ) in the proximate composition of prey. The LMM was implemented with the “lmer” function in the package “ lme4 ” (Bates et al, ) and fitted the logit transformation of the wet mass proportions of P, L and W, and log ratio of the proportion of protein to lipid (lnPL) from each individual prey item, with species ID as a random effect.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) miniaturized video camera deployed on the top of the four central feathers of the tail of a chick‐rearing adult masked booby ( Sula dactylatra tasmani , reproduced with permission from Machovsky‐Capuska et al. ); (b) aerial prey detection of flyingfish ( Exocoetidae spp., reproduced with permission from Machovsky‐Capuska et al. ); (c and d) Undigested individual prey samples collected from regurgitations undergo chemical composition analyses in the laboratory; (e) laboratory measures of prey nutrient content are plotted using amounts‐based nutritional models (see Raubenheimer and Simpson ; Simpson and Raubenheimer ).…”
Section: Macronutrient Balancing In the Wildmentioning
confidence: 99%
“…); (b) aerial prey detection of flyingfish ( Exocoetidae spp., reproduced with permission from Machovsky‐Capuska et al. ); (c and d) Undigested individual prey samples collected from regurgitations undergo chemical composition analyses in the laboratory; (e) laboratory measures of prey nutrient content are plotted using amounts‐based nutritional models (see Raubenheimer and Simpson ; Simpson and Raubenheimer ). The protein:lipid ratios of the three prey species were extracted from the literature; from left to right (yellowtail kingfish ( Seriola lalandi , Machovsky‐Capuska et al.…”
Section: Macronutrient Balancing In the Wildmentioning
confidence: 99%